2014
DOI: 10.1007/s13205-014-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular thermo-alkali-stable laccase from Bacillus tequilensis SN4, with a potential to biobleach softwood pulp

Abstract: Degradation of residual lignin in kraft pulp by chemical bleaching is implicated in causing environmental pollution. The use of thermo- and alkali-tolerant bacterial laccases is considered to be important biological alternative to chemical processing. Laccases from Bacillus species have shown promise in this respect but their intracellular/spore bound presence make their industrial application economically unfeasible. We report here on a novel extracellular active thermo-alkali-stable laccase (SN4 laccase)  wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 29 publications
8
47
0
2
Order By: Relevance
“…Moreover, previous studies have shown maximum laccase activity between 40 and 60°C [38, 39]. The pH profile showed higher laccase activity at 9.0 (266 ± 4.02 U/mL) which is in accordance with Sonica et al [37]. Kuddus et al [26] reported that P. putida laccase exhibited maximum activity at pH 9 (34.45 U/mL) which is also in accordance with the present study results.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, previous studies have shown maximum laccase activity between 40 and 60°C [38, 39]. The pH profile showed higher laccase activity at 9.0 (266 ± 4.02 U/mL) which is in accordance with Sonica et al [37]. Kuddus et al [26] reported that P. putida laccase exhibited maximum activity at pH 9 (34.45 U/mL) which is also in accordance with the present study results.…”
Section: Resultssupporting
confidence: 92%
“…The maximum enzyme activity was observed at 70°C (260.3 ± 6.15 U/mL) using rice bran as a substrate which was well supported by Sonica et al [37] where they have reported comparable activity at 70°C by B. tequilensis using softwood pulp as a substrate. Moreover, previous studies have shown maximum laccase activity between 40 and 60°C [38, 39].…”
Section: Resultssupporting
confidence: 78%
“…It was found that laccase fractions were eluted with 1.0 M NaCl gradient which further purified laccase with 48. 49 Bozoglu et al, 2013;Kaira et al, 2015;Muthukumarasamy et al, 2015;Sondhi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Response surface methodology (RSM) was helpful in enhancement of laccase production several‐fold by critical analysis of each factor, e.g. in the case of B. tequilensis SN4 laccase activity increased about 764‐fold more in comparison with the control in simple medium . Similarly under optimized conditions the activity of laccase from γ‐ Proteobacterium JB gave 9.3‐fold increase over the control…”
Section: Resultsmentioning
confidence: 99%
“…To date, only a few bacterial laccases, especially Bacillus species such as Bacillus safensis DSKK5, B. tequilensis SN4, Bacillus sp. ADR, B. sphaericus and Bacillus (HR03), Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%